SPECIAL FEATURES OF J.R.R. TOLKIEN'S PROSE (ON THE EXAMPLE OF THE “LORD OF THE RINGS”) - Abdusalimov Suhrob Rustamovich (Western European Studies, 2025)
In this article highlights of the peculiarities of Tolkien's prose, in particular the example of the work “The Lord of the Rings”, analyze the peculiarities of his prose. Tolkien's unique world-making skills, mythological fundamentals, attention to language, the image of the struggle between good and evil, as well as the complexity of his characters, are examined. The article reveals Tolkien's prose's outstanding contribution to the genre of fiction and its impact on literature.
Keywords: J.R.R. Tolkien; Lord of the Rings; fiction